Packet waiting time for multiplexed periodic on/off streams in the presence of overbooking. (26th January 2010) - Menth, Michael; Muehleck, Stefan
We present simple approximation formulae for the distribution of the packet waiting time of multiplexed periodic traffic. The multiplexed streams may have different periods and packet sizes. We show by extensive simulations the accuracy of the proposed methods. They are simpler than other existing formulae which make them attractive for engineers, applicable in practice, and easy to implement in switching devices. Packetised speech traffic has a periodic flow structure. Many compression techniques preserve it during talk phases but suppress the generation of packets during silence phases. When such on/off streams are multiplexed, advantage can be taken of their reduced flow rates by overbooking the link bandwidth. We adapt the proposed formulae to cope with on/off traffic and overbooking and validate them by extensive simulations. They can be applied for admission control in networks carrying different types of real-time traffic.